2007
DOI: 10.1211/jpp.59.9.0003
|View full text |Cite
|
Sign up to set email alerts
|

Nose-to-brain delivery of tacrine

Abstract: In the treatment of Alzheimer's disease tacrine, a cholinesterase inhibitor, is not the drug of choice due to its low oral bioavailability, extensive hepatic first-pass effect, rapid clearance from the systemic circulation, pronounced hepatotoxicity, and the availability of drugs better than tacrine in the same pharmacological class. Hence, the aim of this investigation was to ascertain the possibility of direct nose-to-brain delivery of tacrine to improve bioavailability, to avoid the first-pass effect and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Potential use of the nasal route to deliver medications to the brain has been widely investigated, in particular for morphine and also several peptides and proteins (68) or Tacrine®, a cholinesterase inhibitor currently being developed to treat Alzheimer's disease, which has a very low oral bioavailability (9,10). …”
Section: Introductionmentioning
confidence: 99%
“…Potential use of the nasal route to deliver medications to the brain has been widely investigated, in particular for morphine and also several peptides and proteins (68) or Tacrine®, a cholinesterase inhibitor currently being developed to treat Alzheimer's disease, which has a very low oral bioavailability (9,10). …”
Section: Introductionmentioning
confidence: 99%
“…One of the important criteria for establishing whether or not a drug may be useful clinically is the determination of the oral bioavailability of that drug (Jogani et al, 2007; Ohta et al, 2007). Several previous studies have shown that rimonabant is orally active (Huestis et al, 2001; Costa et al, 2005; Davis and Nomikos, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, morphine for cancer pain, lidocaine for migraine, tacrine for Alzheimer's disease and scopolamine for motion sickness (Costantino et al 2007). There are different reasons for choosing intranasal as the dose route of interest, for example, to improve exposure relative to oral administration (apomorphine), to decrease the time to onset of effect by reducing T max , for example, zolmitriptan for migraine (Costantino et al 2007) and also, and maybe more controversial, to provide a direct route via the olfactory epithelium to the brain avoiding the blood-brain barrier and systemic circulation altogether, for example, tacrine, a treatment for Alzheimer's disease (Jogani et al 2007).…”
Section: Discussionmentioning
confidence: 99%